FUNGSI AKTA NOTARIS DALAM LISENSI HKI:PERSPEKTIF FIDUSIA - Cahayani, Dian; Magna, Merlin Swantamalo (UI Scholars Hub, 2021)
This study aims to analyse the function of a notarial deed in an Intellectual Property Rights (IPR) license based on a fiduciary perspective. This type of research is normative legal research by examining secondary data sourced from the principles and theories and laws and regulations. The method of data collection is done by studying literaturesuch as regulations, books, documents or other writings to support this research. The collected data is thenanalyzed qualitatively using data analysis methods. Based on the results of the study it can be concluded that the notary has the authority in making the deed of fiduciary guarantee imposition. Law No. 28of 2014 concerning Copyright (the Copyright Act) has accommodated the provisions of Copyright guarantee as an object of fiduciary security. However, in practice, copyrights which are intangible movable objects, are still difficult to be accepted as fiduciary guarantees in financial institutions in Indonesia. This is because it is not easy to evaluate the economic value of copyrights.